Holter: Monitoring Continuous Integration Practices - Santos, Jadson; Costa, Daniel Alencar da; Kulesza, Uirá (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3604, 2024)
Background: Despite widespread adoption and an extensive body of research evaluating Continuous Integration (CI), there is evidence that not all CI practices are fully adopted. Aims: To help the full adoption of CI, we present in this paper Holter - a tool that automatically calculates and monitors a suite of metrics associated with CI practices. The tool enables developers to continuously access these metrics and receive alerts regarding the evolution of CI practices. Method: We illustrate the usage of our tool for monitoring CI practices and compare the Holter monitoring dashboard with those of existing CI services and third-party tools. Results: Leading CI services and complementary tools still offer basic support for monitoring CI practices. Focusing on monitoring fundamental information related to the performance of the CI pipeline, Holter provides a more comprehensive perspective of CI that cannot be found in other tools. Conclusions: Holter can be used to monitor and improve CI practices in software development projects. Additionally, it can provide an overview of a project’s CI maturity. Video link:  https://doi.org/10.6084/m9.figshare.25880083